2015
DOI: 10.1002/chem.201501713
|View full text |Cite
|
Sign up to set email alerts
|

Highly trans‐Selective Arylation of Achmatowicz Rearrangement Products by Reductive γ‐Deoxygenation and Heck–Matsuda Reaction: Asymmetric Total Synthesis of (−)‐Musellarins A–C and Their Analogues

Abstract: Fully functionalized pyranuloses derived from Achmatowicz rearrangement (AR) are versatile building blocks in organic synthesis. However, access to trans-2,6-dihydropyrans from pyranuloses remains underexplored. Herein, we report a new two-step trans arylation of AR products to access 2,6-trans-dihydropyranones. This new trans-arylation method built on numerous plausible, but unsuccessful, direct arylation reactions, including Ferrier-type and Tsuji-Trost-type reactions, was finally enabled by an unprecedented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 86 publications
0
27
0
Order By: Relevance
“…Having accessed a series of glycosides based on the l ‐rednose scaffold, attention turned to accessing further 2‐amino sugars by synthetic manipulation of the β‐aminoenone unit (Scheme ). Subjecting 4 to standard hydrogenation conditions did not reduce the C=C double bond, instead leading to the 3‐aminopyranone 8 resulting from reductive deoxygenation . In contrast, hydrogenation of the double bond in α‐ 5 was successful, giving α‐ 9 as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…Having accessed a series of glycosides based on the l ‐rednose scaffold, attention turned to accessing further 2‐amino sugars by synthetic manipulation of the β‐aminoenone unit (Scheme ). Subjecting 4 to standard hydrogenation conditions did not reduce the C=C double bond, instead leading to the 3‐aminopyranone 8 resulting from reductive deoxygenation . In contrast, hydrogenation of the double bond in α‐ 5 was successful, giving α‐ 9 as a single diastereomer.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction (Scheme 1) of syringaldehyde (1, 4hydroxy-3,5-dimethoxy-benzaldehyde) with triisopropylsilyl chloride (TIPS-Cl) gave 93% of TIPS-protected 2 30 . Its reaction with malonic acid under Knoevenagel-Doebner conditions furnished (E) configurated cinnamic acid 3.…”
Section: Resultsmentioning
confidence: 99%
“…The allylic electrophiles 16 and 17 were prone to β-elimination which led to the formation of diene side products. A literature search revealed that allyl-aryl coupling reactions in cyclic systems are rare and challenging 3032 , while those in acyclic systems often necessitate elevated reaction temperatures 3335 . Thus, a mild reaction condition for cyclic substrates is highly sought-after.…”
Section: Resultsmentioning
confidence: 99%